1972
DOI: 10.1001/archpedi.1972.02110140101015
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Catch-up Growth After Cushing's Syndrome in Childhood

Abstract: Failure of catch-up in linear growth was experienced by a girl after total adrenal ectomy for Cushing's syndrome. There is a possible correlation between this and failure of catch-up growth in the cortisone-treated rat. The degree of catch-up growth after hyperadrenocorticism may be related to intens¬ ity and duration of glucocorticoid exposure, age of the patient, and individual susceptibil¬ ity of growth mechanisms to damage by ex¬ posure to high levels of glucocorticoids.Compl ete catch-up in linear growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
2

Year Published

1975
1975
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
1
14
1
2
Order By: Relevance
“…Here we decided to focus on Dexa-induced growth retardation since the capacity for catch-up growth after glucocorticoid exposure is of great clinical relevance. Our ex vivo finding that catch-up growth occurs after short-term (7 and 12 days) but not long-term (19 days) Dexa exposure mimics what occurs in children known to display catch-up growth after previous short-term glucocorticoid exposure while prolonged exposure results in incomplete catch-up growth and compromised final height (Mosier et al 1972, Strickland et al 1972. Mechanistic studies, showed that upon cessation of Dexa treatment, the level of chondrocyte proliferation rose above control after short-term exposure (7 days) but not long-term (19 days) exposure, whereas differentiation was unchanged in both cases, suggesting that increased proliferation most likely is the primary local underlying mechanism for the phenomenon of catch-up growth.…”
Section: Discussionmentioning
confidence: 54%
“…Here we decided to focus on Dexa-induced growth retardation since the capacity for catch-up growth after glucocorticoid exposure is of great clinical relevance. Our ex vivo finding that catch-up growth occurs after short-term (7 and 12 days) but not long-term (19 days) Dexa exposure mimics what occurs in children known to display catch-up growth after previous short-term glucocorticoid exposure while prolonged exposure results in incomplete catch-up growth and compromised final height (Mosier et al 1972, Strickland et al 1972. Mechanistic studies, showed that upon cessation of Dexa treatment, the level of chondrocyte proliferation rose above control after short-term exposure (7 days) but not long-term (19 days) exposure, whereas differentiation was unchanged in both cases, suggesting that increased proliferation most likely is the primary local underlying mechanism for the phenomenon of catch-up growth.…”
Section: Discussionmentioning
confidence: 54%
“…It has been proposed that the changes in cartilage produced by growth suppressive levels of glucocorticoids in young animals and humans account for the failure of catch-up growth during recovery (2)(3)(4)(5). However, the results of the present experiments show that both soft tissues and skeletal tissues maintain the capability of supporting catch-up growth after cortisone-induced stunting.…”
Section: Width Of the Tibial Epiphyseal Growth Plate (Experiments I)contrasting
confidence: 50%
“…(Pediatr Res 25373-376, 1989) Abbreviations GH, growth hormone s.c., subcutaneously Treatment of young rats with injections of growth-suppressive doses of cortisone over a period of 4-8 d results in permanent stunting of body size (1). Permanently stunted growth has also been observed in the human after high-dose glucocorticoid treatment (2) or after Cushing's syndrome (3). The absence of catchup growth in the recovery period has been attributed to a failure of response of target tissues to growth factors (4).…”
mentioning
confidence: 99%
“…Evidence support ing the existence of an organismic set point in the rat has been reported by Bernardis et al [19] and Mosier [20], However, quite different results have been observed under conditions of other types of transient growth arrest. For example there is no catch-up growth following growth inhibition induced by glucocorticoid treatment or hypothyroidism (21)(22)(23)(24). In addition, the absence of acute catch-up growth has been observed following GHRH-ab treatment [7,9,12], In these instances, normal or even elevated GH concentrations have been reported.…”
Section: Discussionmentioning
confidence: 99%